2006
DOI: 10.1002/cphc.200600392
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding Tin–Cobalt Interactions in Oxide‐Based Composite Electrodes for Li‐Ion Batteries by Mössbauer Spectroscopy

Abstract: With a view to the development of new composite electrodes for lithium-ion batteries with electroactive tin and cobalt, Co-doped tin dioxide samples are studied. The role played by oxygen and cobalt atoms in the electrochemical behavior of tin-based electrodes for Li-ion batteries is examined by the powerful and selective (119)Sn Mössbauer spectroscopy. For the discharged electrodes, the oxygen atoms in the lithia matrix tend to destabilize the Sn(0) atoms. In contrast, the presence of cobalt atoms helps to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…0.5 mm/s. These values differ from those found for pure lithium-tin alloys (Li 22 Sn 5 , d = 1.837 3 , D = 0.27 2 mm/s) [18] and for lithium-tin alloys obtained from reduction of tin dioxide (d = 1.886 9 , D = 0.63 1 mm/s) [28]. This is in line with the formation of a lithium-cobalt-tin-carbon composite electrode.…”
Section: Electrochemical Reaction Of Tin-based Electrodes With Lithiummentioning
confidence: 38%
“…0.5 mm/s. These values differ from those found for pure lithium-tin alloys (Li 22 Sn 5 , d = 1.837 3 , D = 0.27 2 mm/s) [18] and for lithium-tin alloys obtained from reduction of tin dioxide (d = 1.886 9 , D = 0.63 1 mm/s) [28]. This is in line with the formation of a lithium-cobalt-tin-carbon composite electrode.…”
Section: Electrochemical Reaction Of Tin-based Electrodes With Lithiummentioning
confidence: 38%
“…6Cb), but the quadrupole splitting is high (D = 0.92(5) mm/s). It is worth to note that the Sn(IV) atoms in Co 2 SnO 4 [17] and cassiterite doped with cobalt [32] show high quadrupole splitting values. Metastable tin-oxygen species might be formed in the electrodes that do not correspond to any pure crystalline and stoichiometric compound.…”
Section: Resultsmentioning
confidence: 99%
“…Interactions of tin atoms with both oxygen and cobalt atoms are expected. Tin dioxide, or cobalt-doped tin dioxide, is expected to be reduced at around 1.1-0.9 V [32] following the next reaction:…”
Section: Resultsmentioning
confidence: 99%
“…In tin oxides, this region can be attributed to reactions that form surface films, amorphous lithium oxide, and metallic tin. 4,8,11,[16][17][18][19] The region below 0.9 V can be ascribed to the formation of lithium-tin alloys. The total specific capacity of the first discharge that is observed at 0.2 V is larger for SnO 2 as compared to P-SnO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, previous studies using 119 Sn Mössbauer spectroscopy revealed that at very low discharge rates tin-oxygen interactions are observable in the discharge state, contributing to the instability of the SnO 2 electrode. 18,19 Mindful that the potential of Li-Sn alloying ͑Ͻ0.5 V͒ is sufficiently low to allow side reactions with the electrolyte, 4 we might suggest that electrolyte decomposition and the consequent capacity fade are enhanced at low kinetics, and that the phosphate shell might improve the passivation and formation of a relatively stable solid-electrolyte interface. The SEM micrographs of SnO 2 and P-SnO 2 electrodes after 50 cycles are shown in Fig.…”
Section: A288mentioning
confidence: 98%